NILAI-NILAI KARAKTER DALAM PERTUNJUKAN WAYANG GOLEK PURWA - Sabunga, Barnas (Universitas Pendidikan Indonesia, 2016)
This study aims to explore, examine and identify the character values that were presented in the performance of wayang golek purwa. This research using grounded theory method so that it gives you a chance discovery of a new theory that compiled and verified through systematic data collection, and analysis of data relating to the phenomenon. The values of the characters presented in the wayang golek performance based on value and whence are descended from six life value system include teologik, physical, ethical, aesthetic deserve, logic and teleologik.